Challenges in Implementing STEM Education: Overview from Several Countries - Rizki Amalia Sa'adah; Slamet Suyanto; Nurul Faizah (Postgraduate, University of Mataram, 2025)
This study aims to identify various challenges encountered in implementing STEM education, as well as to describe the problems faced by several countries in implementing STEM education. To achieve the objectives of this study, the researcher conducted a literature review related to STEM education and learning, especially by conducting a Systematic Literature Review (SRL) study. This article is an SLR conducted by accessing the Scopus and Google Scholar databases as sources of information. Scopus and Google Scholar database exploration by entering the keywords